Effects of mineral or protein-energy supplementation and genetic group on metabolism parameters of young beef bulls grazing tropical grass during the rainy season - Simioni, T. A. [UNESP]; Messana, J. D. [UNESP]; Silva, L. G. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Torrecilhas, J. A. [UNESP]; Vito, E. San; Lage, J. F.; Reis, R. A. [UNESP]; Berchielli, T. T. [UNESP] (Elsevier, 2022)
The objective of this study was to evaluate the effects of mineral or protein-energy supplementation and animal genetic groups on rumen fermentation, digestibility and microorganisms of young beef bulls grazing tropical grass during the rainy season. Twelve (nn = 4 per genetic group) ruminally cannulated beef bulls [16 ± 2-months-old and 411 ± 34 kg initial body weight (BW)] were used in a cross-over design, with 4 periods, in a 2 × 3 factorial arrangement. Factors included: 1) two supplementation strategies (SS; mineral supplement [30 g/100 kg BW per day] and protein-energy supplement [300 g/100 kg BW per day]); and 2) three genetic groups (GG; Nellore [NL], ½Angus½Nellore [AN] and Senepol [SN]). Animals were continuously allocated in twelve paddocks composed of Urochloa brizantha (A. Rich.) Stapf. cv. Xaraés for 126 days during the rainy season. Supplementing animals of all GG with protein-energy supplement resulted in an increase of the intake of DM, OM, CP, EE, NFC and ME, and apparent total-tract digestibility of CP and EE. Additionally, animals fed protein-energy supplement showed highest rumen NH3–N concentration, microbial-N synthesis, and retained-N. However, a decrease in rumen pH and acetate:propionate ratio was observed when animals were fed protein-energy supplement. Except for Ruminococcus flavefaciens, the relative abundance of total Archaea and Prevotella.spp. were increased when animals where fed protein-energy supplement. Moreover, a GG effect was observed on the relative abundance of total Archaea, Prevotella.spp. and Ruminococcus flavefaciens, which were highest in NL, SN and AN animals, respectively. SN animals fed protein-energy supplement showed an increase of Streptococcus bovis and Selenomonas ruminantium relative abundance, while Fibrobacter succinogenes and Ruminococcus albus were highest in NL animals supplement mineral and protein-energy supplement, respectively. In conclusion, protein-energy supplementation to beef bulls grazing high-quality tropical grass is an effective strategy to increase rumen fermentation during the rainy season. In addition, it modulated rumen microorganism leading to an increase in the relative abundance of Prevotella.spp., Streptococcus bovis and Selenomonas ruminatium, and a decrease in acetate:propionate ratio in Senepol animals.
Keywords: Archaea; Beef cattle; Digestibility; Rumen bacteria; Tropical forage